Transformation of Waqf in the Digital Era: Qualitative Analysis of Waqf Crowdfunding Models and Cash Waqf Savings Products from the Perspective of Maqashid Syariah - Muslim Marpaung; Irma Suryani Lubis (International Journal of Economics, Management and Accounting, 2024)
This study examines the transformation of waqf in the digital era through the waqf crowdfunding model and cash waqf savings products from the perspective of Maqashid Syariah. Waqf, which is traditionally manifested in the form of immovable assets, has now developed into movable assets such as cash waqf, supported by Law No. 41 of 2004. Digital innovations, such as waqf crowdfunding, allow wider community participation with small amounts for productive social projects, while cash waqf savings products in Islamic banking manage funds productively with the proceeds channeled to education, health, and public infrastructure. Despite having great potential in socio-economic development and in line with the Hifdzu Maal principle in Maqashid Syariah, the implementation of digital waqf still faces challenges such as unclear regulations, lack of public awareness, risk of mismanagement, and limited investment. This study uses a qualitative descriptive approach, case studies, and normative-sociological with in-depth interviews, documentation, and literature studies as data collection techniques. The research subjects were selected through purposive sampling. Data analysis using the Miles and Huberman interactive model, as well as triangulation of sources and methods for data validity. The results of the study are expected to provide theoretical contributions and practical recommendations for the management of digital waqf that is professional, transparent, and beneficial to the community.